Fundamentalism, Multiculturalism and Problems of Conducting Research with Populations in Developing Nations - Crigger, Nancy J (Nursing ethics, 2001)
A growing number of nurse researchers travel globally to conduct research in poor and underserved populations in developing nations. These researchers, while well versed in research ethics, often find it difficult to apply traditional ethical standards to populations in developing countries. The problem of applying ethical standards across cultures is explained by a long-standing debate about the nature of ethical principles. Fundamentalism is the philosophical stance that ethical principles are universal, while the anthropologically-based ‘multicultural’ model claims the philosophical position that principles are culturally bound. The authors explicate the two philosophical stances and advocate a morally sensitive but moderate position of ‘ethical multiculturalism’ rather than favouring either of the above philosophical positions. The final section suggests ways to promote ethical multiculturalism while planning and conducting nursing research.